Tips dan Trik Meningkatkan Profit Selama Pandemi Dengan Peningkatan Skill Sistem Cross Training Pada UMKM Jabar Juara 2021 - Agasti Prior; Sarah Patricia; Agus Nuryana; Hamsinah Hamsinah; Wahyudi Wahyudi (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
Human resource management that is not carried out in an organized manner will certainly be a problem in businesses run by MSMEs. This study aims to increase effectiveness through the development of human resources by cross-training methods. To achieve the target of this activity, an approach was made to the relevant agencies, namely the community of MSME through workshops and socialization as well as training in the form of an explanation about the application of cross-training. After the cross-training was done, the percentage increased in the number of participants with more than one skill to 70% and impacted the output increased from 70 to 80 packs per day. However, there are skills that cannot be developed only through the cross-training method.